YAP activity protects against ventilator-induced lung injury - Liu, Huan; Yang, Xuepeng; Qi, Feng; Li, Xuan; Liu, Yu; Liu, Ge; Lin, Xiaojie (Frontiers in Physiology, 2025)
IntroductionMechanical ventilation (MV) activates inflammatory signaling pathways, leading to ventilator-induced lung injury (VILI), the activation of lung repair processes, persistent inflammatory stimulation and incomplete tissue repair leads to pulmonary fibrosis. The role of Yes-associated protein (YAP) in VILI and related tissue repair mechanisms remains elusive. MethodsWe examined the effects of inhibiting or stimulating YAP activity on VILI, lung repair and fibrosis in a mouse model of MV-induced lung injury. Mice were subjected to either low tidal volume ventilation (LVT) or high tidal volume ventilation (HVT), and HVT was used in subsequent experiments. Additional mice were treated with or without the YAP inhibitor verteporfin (VP) and with or without the YAP stimulator XMU-MP-1 (X) and then subjected to HVT. The severity of lung injury and fibrosis was evaluated via histological analysis; the extent of lung repair was tested by measuring the levels of alveolar epithelial cell (AEC) marker proteins; YAP activity was assessed via Western blotting, immunoprecipitation and immunofluorescence. ResultsMV caused lung injury and fibrosis, decreased the protein expression of AEC markers and β-catenin, increased YAP expression, and the effect of HVT was greater than that of LVT. After inhibition of YAP activity, HVT decreased β-catenin expression, further inhibiting regeneration of AECs and worsening lung injury and fibrosis. In contrast, after stimulation of YAP activity, the reduction in β-catenin was mitigated, the impairment of AEC regeneration was ameliorated, lung injury and fibrosis were alleviated. DiscussionThe results indicate stimulation of YAP activity alleviates VILI by promoting lung repair and inhibiting fibrosis development.